Syntactic Maturity in the English Written texts of Bilingual Students in a Secondary School in Surabaya - TjanHan, Jap; Ngadiman, Agustinus (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2017)
This research was aimed to investigate the syntactic maturity and developmentas manifested in the written texts of bilingual students in a secondary school in Surabaya. This study measured the (1) mean T-unit length, (2) subordinate clause index, (3) mean clause length, (4) mean sentence length, (5) main clause coordination index, and (6) the index of erroneous T-units/total T-units as the indicators of the syntactic maturity. However, it was the mean T-unit length that was used as the main indicator of the syntactic maturity because mean T-unit length was considered to be the most reliable index. The data of the syntactic maturity indicators were obtained by analyzing the descriptive texts that the subjects wrote in response to a writing test instruction. The results of this study have shown that the syntactic maturity and development are influenced by the following four dominant factors: (1) the innate acquisition device enabling the students to acquire English and Indonesian almost simultaneously, (2) the amount of English inputs obtained from parents, teachers, English-immersion program schooling, English movies, books and social media have provided the students with a variety of English resources, (3) the abundant opportunities to produce outputs available at home and at schools have enabled the students to use their English and then modify it during the process of English acquisition, and (4) the individual variations.